ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN USAHA TERNAK SAPI POTONG - Gustina Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2012)
Study the feasibility analysis and development strategy cattle business was conducted to determine the feasibility and development strategy cattle business. The results obtained by the availability of inputs (seeds, enclosures, modern equipment and labor) at the study site. Economically viable cattle business was developed with revenues of Rp 32,274,213 per year with a B / C ratio of 2.03. Development strategy is to improve production and quality (weight) together with livestock agencies.Key words: feasibility, cattle beef cattle, strategy, development